Project DABE: Empathy among Spanish Medical Students - Joaquín García-Estañ; Diego Flores-Funes; Patricia Capdevila-Gaudens; J. Miguel García-Abajo; Mila García-Barbero (Educación Médica, 2022)
Introduction: Empathy refers to an aspect of personality, important in interpersonal relationships and in communication, considered to be an important value in the medical profession. In the present study, we have studied empathy in a sample of more than 5,000 medical students of all 43 medical schools in Spain. Methods: The data belong to the DABE project, a study that included mental health variables and that was applied through a web survey just before COVID-19 pandemic restrictions started. To measure empathy, we used the Jefferson Empathy Scale (Student Version), which comprises 20 items relating to three underlying components, Perspective Taking, Compassionate Care, and Standing in the Patient’s Shoes. Results: Empathy global score was high and it increased progressively every year during medical school. Empathy score was greater in the female students, with a 20% of participants showed high levels of empathy, again more in women. High empathy was associated with students having greater social support, more interest and participation in everyday experiences and satisfaction with social activities. The three components of empathy were also greater in women than in men. Empathy scores were significantly lower in those students that reported smoking and also in the students that reported use of frequent use of cannabis. Discussion: Empathy scores are high in the spanish medical students population, with a 20% of them showing high levels. Empathy scores increase longitudinally during medical school, are greater in female students and lower in those smoking either tobacco or cannabis. Resumen: Introducción: La empatía se refiere a un aspecto de la personalidad, importante en las relaciones interpersonales y en la comunicación, considerado un valor importante en la profesión médica. En el presente estudio, hemos estudiado la empatía en una muestra de más de 5.000 estudiantes de medicina de las 43 facultades de medicina de España. Método: Los datos pertenecen al proyecto DABE, un estudio que incluyó variables de salud mental y que se aplicó a través de una encuesta web justo antes de que comenzaran las restricciones pandémicas del COVID-19. Para medir la empatía, utilizamos la escala de empatía de Jefferson (versión para estudiantes), que consta de 20 ítems relacionados con tres componentes subyacentes: toma de perspectiva, atención compasiva y ponerse en los zapatos del paciente. Resultados: La puntuación global de empatía fue alta y aumentó progresivamente cada año durante la estancia en la facultad de medicina. La puntuación de empatía fue mayor en las alumnas, con un 20% de los participantes que mostraron altos niveles de empatía, nuevamente más en las mujeres. La alta empatía se asoció con que los estudiantes tengan un mayor apoyo social, más interés y participación en las experiencias cotidianas y satisfacción con las actividades sociales. Los tres componentes de la empatía también fueron mayores en las mujeres que en los hombres. Las puntuaciones de empatía fueron significativamente más bajas en los estudiantes que informaron haber fumado y también en los estudiantes que informaron el uso frecuente de cannabis. Discusión: El nivel de empatía es alto en la población de estudiantes de medicina españoles, con un 20% de ellos mostrando niveles muy altos. El nivel de empatía aumenta longitudinalmente durante el tiempo en la facultad de medicina, es mayor en las estudiantes y más bajos en aquéllos que fuman tabaco o cannabis.